Fator de impacto dos periódicos científicos brasileiros indexados na web of science - COUTO, Cleber William Silva (2021)
It analyzes the importance of measurement in scientific production highlighting the main academic indicators and giving emphasis the Impact Factor (FI). For the application of the metric was used the main tool of scientific communication, the scientific journal. Proposes as general objective to present the IF of the Brazilian scientific journals by means of the verification of indexed titles in the Web of Science (WoS), identification of the number of Brazilian journals in the several areas of knowledge and description of indexed titles in the base. The methodology of the work how much to objectives, presents a descriptive character, with one a quantitative approach, being used the bibliographic research for the data collection, aiming at a better theoretical foundation on the subject. It presents studies and discussions about FI using some authors who work with the subject. shows some sources of printed and electronic information used in the middle academic environment in which it is possible to retrieve Brazilian scientific journals. It concludes by showing in detail the FI of the Brazilian securities indexed in WoS, as well as exposing details and importance of these values to the scientific community.